PENGARUH OVARIEKTOMI TERHADAP GAMBARAN HISTOPATOLOGIS GINJAL TIKUS - , AYU DEWI PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Ovariectomy caused reduction to estrogen quantity, lowering calcium reabsorbtion in renal tubulus and cause the increment of calcium excretion of urine. This research was done to review the effect of ovariectomy upon the histological appearance of wistar rats kidney. Ten female wistar rats, eight week years old, divided into two groups those are non ovariectomizwd and ovariectomized group. Each five rats were standard feed and drink of aquabidestilata in ad libitum. Rats weve placed in solitary cage in a room 22-25 0 C for eight weeks. In the end of tretment, rats were euthanized, left kidney were taken for histhopathological checking with HE stain and analized descriptively. The result from histopathological checking showed that both groups kidneys single layer squamus epithel over their capsula bowman, spatium capsulare between stratum parietale and stratum viscerale, proximal convulatus tubulus was confered by single layer cuboidal epithelial with eosinophilic appearance and distal convulatus tubulus was surrounded by cuboidal epithelial cell. From the research, we conclude that ovariectomy gave no effect upon kidneys histopathological appearance.